A hemiparasite in the forest understorey: photosynthetic performance and carbon balance of Melampyrum pratense. (19th October 2017) - Světlíková, P.; Hájek, T.; Těšitel, J.
Abstract: Melampyrum pratense is an annual root‐hemiparasitic plant growing mostly in forest understorey, an environment with unstable light conditions. While photosynthetic responses of autotrophic plants to variable light conditions are in general well understood, light responses of root hemiparasites have not been investigated. We carried out gas exchange measurements (light response and photosynthetic induction curves) to assess the photosynthetic performance of M. pratense in spring and summer. These data and recorded light dynamics data were subsequently used to model carbon balance of the hemiparasite throughout the entire growth season. Summer leaves had significantly lower rates of saturated photosynthesis and dark respiration than spring leaves, a pattern expected to reflect the difference between sun‐ and shade‐adapted leaves. However, even the summer leaves of the hemiparasite exhibited a higher rate of light‐saturated photosynthesis than reported in non‐parasitic understorey herbs. This is likely related to its annual life history, rare among other understorey herbs. The carbon balance model considering photosynthetic induction still indicated insufficient autotrophic carbon gain for seed production in the summer months due to limited light availability and substantial carbon loss through dark respiration. The results point to potentially high importance of heterotrophic carbon acquisition in M. pratense, which could be of at least comparable importance as in other mixotrophic plants growing in forests – mistletoes and partial mycoheterotrophs. It is remarkable that despite apparent evolutionary pressure towards improved carbon acquisition from the host, M. pratense retains efficient photosynthesis and high transpiration rate, the ecophysiological traits typical of related root hemiparasites in the Orobanchaceae.